The effect of organizational cynicism on deviant behaviors in the workplace through organizational silence and destructive leadership (Case Study: Islamic Azad University, Isfahan Branch) - Reza Ebrahimzadeh Dastjerdi; Abbas Ghaedamini Harouni; Ali Reza Ebrahimpour (Pizhūhish/hā-yi rahbarī va mudīriyyat-i āmūzishī, 2019)
The purpose of this study was to investigate the impact of organizational cynicism on deviant behaviors in the workplace through organizational silence and destructive leadership. The purpose of this study was applied and descriptive correlational in terms of data collection. The statistical population of this study consisted of 1000 employees of Islamic Azad University, Isfahan, Iran. The sample consisted of 287 individuals selected through Cochran sampling formula by proportional stratified sampling method. (And standard deviant behaviors questionnaire at workplace (Bennett & Robinson (2000)) and the Vakula & Brados Organizational Silence Questionnaire (2005) and Golparvar's malicious leadership standard questionnaire (2014). Experts, a formality based on the views of a number of statistical population and constructs were evaluated by factor analysis method and after validity of the necessary terms were confirmed. On the other hand, the reliability of the questionnaires with Cronbach's alpha method were (0.88), (0.85), (0.89), respectively were estimated. Data were analyzed at the inferential level including structural equation modeling. The results showed that organizational cynicism has a positive and significant effect on deviant behaviors in the workplace through organizational silence, which has a coefficient of 0.55, and through destructive leadership, it has a positive and significant effect on deviant behaviors in the workplace. It is 0.44 and also organizational cynicism has a positive and significant effect on deviant behaviors in the workplace which has a coefficient of 0.88.